Pengaruh Kepuasan Kerja Dan Beban Kerja Terhadap Kinerja Kerja Karyawan Pada PT. Bank Mandiri (Persero), Tbk Cabang Daan Mogot Jakarta - Isyana Emita (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
This study aims to find and produce an analysis of the effect of job satisfaction and workload on employee performance at PT Bank Mandiri (Persero) Tbk Daan Mogot Branch Jakarta. Respondents in this study were employees who worked in the PT. Bank Mandiri (Persero), Tbk Daan Mogot Jakarta Branch. The number of respondents who became the sample in this study were 67 people and based on the random sampling method. This study uses multiple linear regression analysis techniques or models with the help of SPSS 26 software. Based on the above method, the results of this study indicate that Job Satisfaction and Workload have a significant influence partially or simultaneously on employee performance at PT Bank Mandiri (Persoro). Tbk Daan Mogot Jakarta Branch. and the percentage shows that 57% of employee performance can be explained by job satisfaction and workload